Sub-Chronic Methomyl Exposure Induces Oxidative Stress and Inflammatory Responses in Zebrafish with Higher Female Susceptibility - Mingxiao Li; Xi Chen; Chao Song; Jing Xu; Limin Fan; Liping Qiu; Dandan Li; Huimin Xu; Shunlong Meng; Xiyan Mu; Bin Xia; Jun Ling (MDPI AG, 2024)
The widespread use of carbamate pesticides has raised significant environmental and health concerns, particularly regarding water contamination and the disruption of defense systems in organisms. Despite these concerns, research on the differential impacts of pesticides on male and female organisms remains limited. This study focused on methomyl, investigating sex-specific differences in liver antioxidant defenses and inflammatory response indices in male and female zebrafish after 56 days of exposure to environmentally relevant concentrations (0, 0.05, 0.10, and 0.20 mg/L). Our findings indicate that methomyl exposure significantly increased ROS content in zebrafish livers, inducing oxidative stress and activating enzymatic antioxidant defenses such as SOD, CAT, and GSH-Px activities. Sub-chronic exposure altered the expression of apoptosis-related genes (Bax/Bcl2a and Caspases3a), resulting in liver cell apoptosis in a concentration-dependent manner, with the 0.20 mg/L concentration causing the most severe damage. Additionally, methomyl exposure at environmentally relevant concentrations triggered persistent inflammatory responses in liver tissues, evidenced by increased transcription levels of inflammatory factor genes and the activation of toll-like receptors, heightening susceptibility to exogenous allergens. It is noteworthy that oxidative damage indicators (AST, ROS, MDA) and inflammatory gene expressions (IL-1β, TNF-α) were significantly higher in female livers compared to male livers at 0.10-0.20 mg/L methomyl exposure. Consequently, our study underscores the potential adverse effects of environmental methomyl exposure on aquatic organisms and highlights the need for heightened consideration of the risks posed by environmental endocrine disruptors to female health and safety.